EXPERIENCE OF DEVELOPMENT OF EDUCATIONAL PROGRAM "MUSIC EDUCATION" - Sapieva, M.S.; Kuskadamova, K.S. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article is devoted to the problem of developing of a modular educational program in the specialty "Music Education". The analysis of the content of special training of future music teachers is carried out, the ratio of credits for psychological, pedagogical and special training of graduates is presented. Keywords: Musical education, educational program, modules
Keywords: Musical education; educational program; modules; competences; special training